2020
DOI: 10.1101/2020.03.13.990457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria in Southern Venezuela: The Hottest Hotspot in Latin America

Abstract: Malaria cases in Latin America reached ~1 million in 2017 and 2018, with 53% and 51% reported from Venezuela, respectively. In this study, we characterized the spatiotemporal dynamics of malaria transmission between 2007-2017 in southern Venezuela, the main endemic area of the country. We found that disease transmission was focal and more prevalent in the southeast of southern Venezuela where two persistent hotspots of Plasmodium vivax (76%) and P. falciparum (18%) linked to deforestation for illegal gold mini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 44 publications
0
39
0
2
Order By: Relevance
“…As reported previously [10,29,31,32], most of the women were young, with several of them being adolescents, re ecting the fertility rate reported for Venezuela, the highest in Latin America, with 85 births per 1,000 adolescents aged between 15-19 years old in 2018 [33]. Similar to reported in Bolívar state [9], most of the women are from Angostura del Orinoco and Sifontes municipality, which perhaps be related to the continuous migration of individuals from the community to gold mining areas, contributing to the malaria transmission [19,21,31].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As reported previously [10,29,31,32], most of the women were young, with several of them being adolescents, re ecting the fertility rate reported for Venezuela, the highest in Latin America, with 85 births per 1,000 adolescents aged between 15-19 years old in 2018 [33]. Similar to reported in Bolívar state [9], most of the women are from Angostura del Orinoco and Sifontes municipality, which perhaps be related to the continuous migration of individuals from the community to gold mining areas, contributing to the malaria transmission [19,21,31].…”
Section: Discussionmentioning
confidence: 85%
“…In Bolívar state, 70-80% of malaria cases are caused by P. vivax, and 20-30% are due to P. falciparum [19]. Recently, it has been reported that municipalities in Bolívar State have a heterogeneous annual parasitic incidence (API), with some hotspots in the southeast part [21]. For epidemiological week N° 52 of 2016, the API was 101.7 per 1,000 inhabitants in this state [22].…”
Section: Study Areamentioning
confidence: 99%
“…Populations of border towns are generally more vulnerable, especially those living in remote areas, as recently observed along the border between French Guiana and Brazil where local inhabitants were affected by a malaria outbreak [37]. Recent events in Venezuela, causing mass migrations, has been responsible for an increase in malaria transmission across the frontier between Brazil and Venezuela [30,31]. Each one of these scenarios demand unique malaria control programs, that include vector-control measures adapted to the regional context.…”
Section: Malaria Vectors In the Brazilian Amazon And The Importance Omentioning
confidence: 96%
“…However, in 2017 and 2018, 197 and 207 thousand cases were registered respectively, a considerable growth compared to previous years [7]. The recent increase in reported malaria cases is mostly due to transmission occurring near the borders between Brazil and its neighbors French Guiana and Venezuela [30,31,32]. A timeline of malaria in the Brazilian Amazon is presented in figure 1.…”
Section: Malaria In Brazil a Brief History And Current Statusmentioning
confidence: 99%
“…For example, illegal gold mining in the rainforest attracts non-immune workers into settler communities with inadequate healthcare, which has led to hotspots of malaria resurgence in Venezuela. 21 22 …”
Section: New Opportunities For Mosquitoes To Thrivementioning
confidence: 99%